2005
DOI: 10.1007/s10552-004-3074-9
|View full text |Cite
|
Sign up to set email alerts
|

Regular use of aspirin or acetaminophen and risk of non-Hodgkin lymphoma

Abstract: Regular use of aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) has been hypothesized to be associated with reduced risk of non-Hodgkin lymphoma (NHL), although previous results have been inconsistent. The current study investigated the effects of regular aspirin or acetaminophen use on non-Hodgkin lymphoma risk among 625 individuals with primary, incident NHL and 2512 age and sex matched hospital controls with non-neoplastic conditions who completed a comprehensive epidemiologic questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Some prospective cohort and case-control studies analyzed the association between aspirin and non-aspirin NSAID use and risk of NHL with contradictory results. An inverse association was documented in a population-based casecontrol study (OR=0.72; 95% CI= 0.56-0.91) (Holly et al, 1999) and a near significant association between regular use of aspirin and moderate decrease of NHL has also been reported in another hospital-based case-control study in men (OR= 0.82; 95% CI= 0.65-1.04), while women who used acetaminophen regularly experienced a 71% elevation in the risk of B-cell NHL (OR= 1.71; 95% CI 1.18-2.50) (Baker et al, 2005). A potential protective effect of analgesic use on NHL risk in women but not in men has also been reported (Beiderbeck et al, 2003).…”
Section: Nsaids and Steroidssupporting
confidence: 66%
“…Some prospective cohort and case-control studies analyzed the association between aspirin and non-aspirin NSAID use and risk of NHL with contradictory results. An inverse association was documented in a population-based casecontrol study (OR=0.72; 95% CI= 0.56-0.91) (Holly et al, 1999) and a near significant association between regular use of aspirin and moderate decrease of NHL has also been reported in another hospital-based case-control study in men (OR= 0.82; 95% CI= 0.65-1.04), while women who used acetaminophen regularly experienced a 71% elevation in the risk of B-cell NHL (OR= 1.71; 95% CI 1.18-2.50) (Baker et al, 2005). A potential protective effect of analgesic use on NHL risk in women but not in men has also been reported (Beiderbeck et al, 2003).…”
Section: Nsaids and Steroidssupporting
confidence: 66%
“…5). In general, previous cohort studies reported positive (4,5,7) or null (19,20) associations between NSAID use and NHL whereas most case-control studies reported inverse (8)(9)(10)(11)15), associations. Potential recall bias in the case-controls studies may have influenced the study results and contributed to these inconsistent findings.In analyses by NHL subtype, we observed an association between current use of 60þ pills/month of NSAIDs use and increased risk of follicular lymphoma that persisted when NSAID exposure was lagged and was strongest for long-term, regular NSAID users.…”
Section: Discussionmentioning
confidence: 91%
“…However, results of epidemiologic studies of nonsteroidal anti-inflammatory drugs (NSAIDs) in relation to non-Hodgkin lymphoma (NHL) are inconsistent. Positive, negative, and null associations have been reported, with some studies reporting an association with all NSAIDs, whereas others with just aspirin or nonaspirin NSAIDs (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Most studies had limited statistical power, particularly for detailed analyses by frequency, duration, and type of NSAID use, and/or NHL subtype.…”
Section: Introductionmentioning
confidence: 99%
“…There was no way to ascertain whether or not those individuals who refused to complete the instrument differed from participants with respect to aspirin use. Nevertheless, previous studies that used the PEDS database and looked at effects of aspirin on variety of cancer sites like ovary, colon, pancreas, breast, nonHodgkin lymphoma and lung 30,32,[68][69][70][71] consistently replicated established epidemiological associations. Moreover, the descriptive characteristics of the subjects (Table I) are consistent with well documented reports in the literature, [10][11][12] suggesting that the results may be generalized to a larger population.…”
Section: Discussionmentioning
confidence: 99%